Rendition - Golin, Steve; Viscidi, Marcus; Sane, Kelley; Hood, Gavin; Gyllenhaal, Jake, 1980-; Witherspoon, Reese, 1976-; Sarsgaard, Peter; Metwally, Omar; Naor, Yigal; Khouas, Moa; Oukach, Zineb; Arkin, Alan; et al. ([Burbank, Calif.] : New Line Home Entertainment, 2008)
The policy of "extraordinary rendition" allows for handing over of suspected terrorists to countries that use torture as an interrogation tool. Anwar El-Ibrahimi is an Egyptian born man who disappears on a flight from Africa to Washington, DC. He is sent to a North African country where torture is practiced and the CIA gives approval.
English track: Dolby digital 5.1.
Title from disc label.
Originally released as a motion picture in 2007.
Special features: 'Outlawed' documentary; 'Intersections: the making of Rendition' documentary; deleted scenes including an alternate ending; director commentary; theatrical trailer; sneek peaks.
Director of photography, Dion Beebe ; editor, Megan Gill ; music, Paul Hepker, Mark Kilian ; costume designer, Michael Wilkinson ; production designer, Barry Robison.
Jake Gyllenhaal, Reese Witherspoon, Peter Sarsgaard, Omar Metwally, Yigal Naor, Moa Khouas, Zineb Oukach, Alan Arkin, Meryl Streep.
Keywords: United States. -- Central Intelligence Agency -- Drama; Extraordinary rendition -- United States -- Drama; Political prisoners -- Abuse of -- Africa, North -- Drama; Questioning -- Africa, North -- Drama; Africa, North -- Drama; Films for the hearing impaired; Suspense films; Feature films